On the solvability of boundary value problem for mixed-type equation with a singular coefficient - Menglibay Kh Ruziev (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2014)
In this paper we study a problem with conditions on the inner characteristic and on some parts of the degeneration line for mixed type equation with singular coefficient in unbounded domain. We prove the uniqueness of solution of the mentioned problem with the help of the extremum principle. The proof of the existence of solution is based on the theory of singular integral equations and Fredholm integral equations.